Effect of Different Rice Varieties on Changes in Anthocyanin Content and Physical Properties of Zongzi Products - Parnsakhorn, Sunan; Langkapin, Jaturong (Frontiers in Engineering Innovation Research, 2022)
This research was to study the effect of different rice varieties on changes in anthocyanin content and physical properties of Zongzi products. White glutinous rice, black sticky rice and riceberry rice were used in this study, divided into the first sample 100% white glutinous rice, the second sample: white glutinous rice mixed with black sticky rice 50% each, the third sample white glutinous rice mixed with riceberry rice 50% each and the fourth example black glutinous rice mixed with riceberry rice 50% each. It was found that the use of 100% white glutinous rice had the lowest water activity content of 0.854, while the water activity content of glutinous rice mixed with the formula showed water activity content between 0.888-0.929. Also, related to the moisture content with similar values ​​in all 4 samples (51.30-57.25%wb). The condition of 100% white glutinous rice showed, the highest hardness of 32.14 N, while the black sticky rice mixed with riceberry rice gave the lowest value at 8.97 N. For sensory test in all 4 samples, it was found that black glutinous rice mixed with riceberry rice presented score at the level of like moderately to like very much (6.60-7.57), in terms of appearance, odor, color, taste and overall preference. The color test showed that 100% white glutinous rice gave the highest L* value and tended to decrease when mixed with other types of rice and the same results were presented as the yellowness value (b*), while the redness value (a*) increased when mixed with black sticky rice and riceberry rice. For anthocyanin determination, 100% white glutinous rice contained the lowest anthocyanin content of 0.063 g/g dry weight. While riceberry rice and black sticky rice were found that their anthocyanin contents increased and the value was between 0.193-0.220 g/g dry weights.